Application of AI in Healthcare and Medical Treatment - Singh, Shiv Kumar; Jangid, Mohit (International Journal of Psychosocial Rehabilitation, 2019)
Artificial Intelligence (AI) has emerged as a transformative force in healthcare, revolutionizing various components of affected person care, diagnostics, drug development, administrative processes, and more. Its integration has the capacity to enhance effects, lessen costs, and decorate the overall performance of healthcare structures worldwide. Artificial Intelligence (AI) has come up as a groundbreaking generation revolutionizing the panorama of healthcare shipping and management. This paper explores the multifaceted packages of AI in healthcare, highlighting its transformative effect on numerous aspects of patient care, diagnostics, treatment making plans, and administrative procedures. Through the analysis of AI-pushed improvements together with predictive analytics, herbal language processing, laptop vision, and system gaining knowledge of algorithms, this look at examines their pivotal position in enhancing diagnostic accuracy, personalised treatment approaches, and operational efficiencies inside healthcare structures. Furthermore, this summary discusses the challenges and ethical concerns associated with the combination of AI in healthcare, emphasizing the need for responsible implementation, regulatory frameworks, and ongoing assessment to make sure patient protection, statistics privacy, and equitable get right of entry to AI-enabled healthcare solutions. In end, the paper underscores the significant capability of AI to revolutionize healthcare delivery, improve affected person results, and form the future of drugs while advocating for a balanced technique that harnesses its abilities even as addressing inherent demanding situations.